Restraining reactive oxygen species in Listeria monocytogenes promotes the apoptosis of glial cells. (4th July 2017) - Li, Sen; Li, Yixuan; Chen, Guowei; Zhang, Jingchen; Xu, Fei; Wu, Man
Abstract : Objectives : Listeria monocytogenes is a facultative anaerobic foodborne pathogen that can traverse the blood–brain barrier and cause brain infection. L. monocytogenes infection induces host cell apoptosis in several cell types. In this study, we investigated the apoptosis of human glioma cell line U251 invaded by L. monocytogenes and evaluated the function of bacterial reactive oxygen species (ROS) during infection. Methods : Bacterial ROS level was reduced by carrying out treatment with N -acetyl cysteine (NAC) and diphenyleneiodonium chloride (DPI). After infection, the apoptosis of U251 cells was examined by flow cytometry assay and propidium iodide staining. Results : DPI and NAC efficiently decreased ROS level in L. monocytogenes without affecting bacterial growth. Moreover, the apoptosis of glial cells was enhanced upon invasion of DPI- and NAC-pretreated L. monocytogenes . Discussion : Results indicate that the apoptosis of glial cells can be induced by L. monocytogenes, and that the inhibition of bacterial ROS increases the apoptosis of host cells.